Vallejo Yesterdays: 20 Yeas Ago from the Chronicle Files - Vallejo News Chronicle (Vallejo News Chronicle)
20 years ago today: The name of the California Nautical School which may soon be located in Vallejo has been changed to the California Maritime Academy as a result of recent legislation, it was learned today.